Best Answer

given the identity sin(x+y)=sinx cosy + siny cosx

sin2x = 2 sinx cosx and

sin(2(x)+x) = sin 2x cos x + sinx cos 2x

using the last two identities gives

sin3x= 2 sinx cosx cosx + sinx cos2x

factoring the sinx we have

sin3x = sinx(2cosx cosx+cos2x)

which satisfies the requirement.

However, we can simplify further since cos 2x = cosx cosx - sinx sinx (a well known identity)

sin3x = sinx (2cosx cosx +cosx cosx - sinx sinx)

so sin3x= sinx(3cosx cosx - sinx sinx)

or sin 3x = 3.cosÂ²x.sinx - sinÂ³x

* * * * *

Good, but not good enough. The answer was required in terms of sin, not a mixture of sinx and cosx. Easily recitified, though, since cos²x = 1 - sin²x

Therefore sin3x = 3*(1-sin²x)*sinx - sin³x

= 3sinx - 4sin³x

🙏

🤨

😮

Study guides

☆☆

Q: What is sin 3x in terms of sin x?

Write your answer...

Submit

Still have questions?

Related questions

Using Euler's Formula, you use (cos(x) + i sin(x))^n = cos (nx) + i sin(nx) Now you let n=3 (cos(x) + i sin (x))3 = cos(3x) + i sin (3x) (cos(x))3 + 3(cos(x))2 * i sin(x) + 3cos(x) * i2 (sin(x))3 = cos(3x)+ i sin(3x) (cos(x))3 + i(3sin(x)(cos (x))2) - 3cos(x)(sin(x)2) - i(sin(x))3 = cos (3x) + i sin(3x) Now only use the terms with i in them to figure out what sin(3x) is... 3sin(x)(cos(x))2 - (sin(x))3 = sin(3x) Hope this helps! :D

I think you mean to solve:(-2 cos23x) - (3 sin 3x) = 0cos2 x + sin2 x = 1⇒ cos2x = 1 - sin2 x⇒ -2 cos2 3x - 3 sin 3x = -2(1 - sin2 3x) - 3 sin 3x = 0⇒ 2 sin2 3x - 3 sin 3x - 2 = 0⇒ (2 sin 3x + 1)(sin 3x - 2) = 0⇒ sin 3x = -1/2 or 2sin 3x = 2 is impossible as the range of sine is -1 ≤ sine ≤ 1Thus:sin 3x = -1/2⇒ 3x = 2nπ - π/6 or 2nπ - 5π/6⇒ x = 2/3nπ -π/18 or 2/3nπ -5π/18

y= sin 3x

3x + x = 4x

The derivative of y = sin(3x + 5) is 3cos(3x + 5) but only if x is measured in radians.

convert tan^2x into sin^2x/cos^2x and secant x into 1/cos x combine terms for integral sin^2x/cos^3x dx then sub in u= cos^3x and du=-2sin^2x dx

Yes, 3x and x are like terms because they have the same variable raised to the same power.

sin(3x) = 3sin(x) - 4sin^3(x)

You need to know the trigonometric formulae for sin and cos of compound angles. sin(x+y) = sin(x)*cos(y)+cos(x)*sin(y) and cos(x+y) = cos(x)*cos(y) - sin(x)*sin(y) Using these, y = x implies that sin(2x) = sin(x+x) = 2*sin(x)cos(x) and cos(2x) = cos(x+x) = cos^2(x) - sin^2(x) Next, the triple angle formulae are: sin(3x) = sin(2x + x) = 3*sin(x) - 4*sin^3(x) and cos(3x) = 4*cos^3(x) - 3*cos(x) Then the left hand side = 2*[3*sin(x) - 4*sin^3(x)]/sin(x) + 2*[4*cos^3(x) - 3*cos(x)]/cos(x) = 6 - 8*sin^2(x) + 8cos^2(x) - 6 = 8*[cos^2(x) - sin^2(x)] = 8*cos(2x) = right hand side.

sin7x-sin6x+sin5x

0. sin 2x = cos 3x 1. sin 2x = sin (pi/2 - 3x) [because cos u = sin (pi/2 - u)] 2. [...]

3x-12=12 express the equation in terms of x, 3x=12+12 then, perform the operation 3x=24 x=8 that is now the value of x.

Two terms of an expression

Collect like terms together: 3x - 7 - 4 - x = (3x - x) + (-7 - 4) = (3 - 1)x + (-11) = 2x - 11

Take 3x + 7y - x + 12y as an example. Collecting similar terms gives 3x - x + 7y + 12y ie 2x + 19y. Get it?

It is 9.1 inches (approx). L*[sin(x) + sin(2x) + sin(3x) +sin(4x)] = 28 inches where x = 360/10 = 36 degrees. Since x = 36 deg, sin(x) = sin(4x) and sin(2x) = sin(3x) So L*[2sin(x) + 2sin(2x)] = 28 inches L*[sin(x) + sin(2x)] = 14 inches L* 1.539 = 14 approx so that L = 9.098 inches or 9.1 inches, approx.

Multiply each term of the second expression by each of the terms in the first expression and add them together, collecting like terms together: (x - 6)(3x² + 10x - 1) = x(3x² + 10x - 1) + (-6)(3x² + 10x - 1) = (3x³ + 10x² - x) + (-18x² - 60x + 6) = 3x³ + 10x² - 18x² - x - 60x + 6 = 3x² + (10 - 18)x² + (-1 - 60)x + 6 = 3x² - 8x² - 61x + 6

y = 2 sin 3x y' = 2(sin 3x)'(3x)' y' = 2(cos 3x)(3) y' = 6 cos 3x

Take f(x) = cos(3x) ∫ f(x) dx = ∫ cos(3x) dx Take u=3x → du = 3dx = ∫ 1/3*cos(u) du = 1/3*∫ cos(u) du = 1/3*sin(u) + C, C ∈ ℝ = 1/3*sin(3x) + C

7

There are 4 terms in the given expression

cos(x) = sin(pi/2-x) = -sin(x-pi/2)

to find sin 35 here we take the angle = x=15 then 3x=45 , 4x=60 then 4x-3x=60-45 then by putting sin on rhs we will get cos 35 and sin 35 hope it helped you

y = (x^2)(sin x)(2x)(cos x) - 2sin xy' = [[(x^2)(sin x)][(2x)(cos x)]]' - (2sin x)'y' = [[(x^2)(sin x)]'[(2x)(cos x)] + [(2x)(cos x)]'[(x^2)(sin x)]]- (2sin x)'y' = [[(x^2)'(sin x) + (sin x)'(x^2)][(2x)(cos x)] + [(2x)'(cos x) + (cos x)'(2x)][(x^2)(sin x)] ] - 2(cos x)y' = [[(2x)(sin x )+ (cos x)(x^2)][(2x)(cos x)] + [2cos x - (sin x)(2x)][(x^2)(sin x)]] - 2(cos x)y' = (4x^2)(sin x cos x) + (2x^3)(cos x)^2 + (2x^2)(sin x cos x) - (2x^3)(sin x)^2 - 2cos xy' = (6x^2)(sin x cos x) + (2x^3)(cos x)^2 - (2x^3)(sin x)^2 - 2cos x (if you want, you can stop here, or you can continue)y' = (3x^2)(2sin x cos x) + (2x^3)[(cos x)^2 - (sin x)^2] - 2cos xy' = (3x^2)(sin 2x) + (2x^3)(cos 2x) - 2 cos xy' = (2x^3)(cos 2x) + (3x^2)(sin 2x) - 2 cos x

Simplifying 3x = 5 Solving 3x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667 or x = 1 2/3

People also asked